Increase in CO2 Uptake Capacity in the Arctic Chukchi Sea During Summer Revealed by Satellite‐Based Estimation. Issue 15 (31st July 2021) - Tu, Zebin; Le, Chengfeng; Bai, Yan; Jiang, Zongpei; Wu, Yingxu; Ouyang, Zhangxian; Cai, Wei‐Jun; Qi, Di
Abstract: The capacity of CO2 uptake in the Chukchi Sea is particularly sensitive to rapid physical and biological changes. However, scarce field observations pose a challenge in understanding the long‐term trend of CO2 uptake capacity on this continental shelf. We adopted a machine‐learning‐based approach to construct a 17‐years (2003–2019) long‐term time series of summer sea surface partial pressure of CO2 ( p CO2 ) from remote sensing products. We show that the long‐term increase in CO2 uptake capacity can be attributed to strong and enhanced biological uptake. In addition, the intraseasonal variability of surface p CO2 in early summer confirms the crucial role of sea ice melt and the subsequently enhanced photosynthesis as soon as the surface ocean converts into an open system. Our results thus highlight the use of remote sensing data in interpolating/extrapolating the highly dynamic carbonate system in the continental shelf sea and shed light into future studies involving machine learning or algorithms. Plain Language Summary: The climate change in the recent decades has caused remarkable sea surface warming in the Arctic Ocean, with its warming rate twice higher than the global average. The Arctic warming could have some consequences such as shrinkage of sea ice and increase of freshwater storage which profoundly affect the carbon cycle in the Arctic Ocean. The Chukchi Sea serves as the largest oceanic CO2 sink in the Arctic Ocean, yet its long‐term variation and associated mechanism remain unclear due to undersampling. In this study, we adopted a machine‐learning‐based model to construct a 17‐years long‐term time series of sea surface partial pressure of CO2 ( p CO2 ) from satellite observations. Results showed that the CO2 uptake capacity in the Chukchi Sea has increased in the recent decades, primarily owing to the increased primary productivity. This study demonstrated the great potential of ocean color remote sensing in retrieving key biogeochemical parameters in polar regions, and providing a powerful tool for monitoring carbonate system for the oceanographic community. Key Points: A machine learning approach was calibrated and validated to obtain sea surface p CO2 from satellite observations in the Chukchi Sea Increase in CO2 uptake capacity is revealed by a 17‐years (2003–2019) long‐term time series of summer p CO2 Strong and enhanced biological uptake contribute to the increase in CO2 uptake capacity